GLOBAL TRIGGERS AND IMPERATIVES FOR THE FORMATION OF CIRCULAR VALUE CHAINS TO ENHANCE THE RESILIENCE OF THE NATIONAL ECONOMY IN THE CONTEXT OF EUROPEAN INTEGRATION - IATSENKO, Oleksandr; YATSENKO, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The global economy is currently undergoing profound transformations driven by a combination of global challenges — resource constraints, climate risks, geopolitical instability, and disruptions in global supply chains. The traditional linear model of production and consumption, which for a long time ensured economic growth, is gradually losing its viability, giving rise to new crisis phenomena. This situation emphasizes the need to develop new approaches to organizing economic processes based on the principles of sustainable development, resource efficiency, and innovation. In this context, circular value-added chains are viewed as a strategic direction for the modernization of both global and national economies, as they involve closed resource-use cycles, material reuse, the development of industrial symbiosis, and the implementation of innovative business models. The formation of such chains is determined by the influence of global triggers — from environmental and technological to geo-economic ones — that set the imperatives for the transformation of the modern economic system. For Ukraine, the relevance of this issue is reinforced by the necessity to reduce dependence on imports of critical resources, increase competitiveness in the process of integration into the European economic space, and strengthen the resilience of the national economy to global crises.The purpose of the study is to substantiate the global triggers and strategic imperatives for the formation of circular value-added chains and to develop a model for their implementation in order to enhance the resilience and competitiveness of the national economy. The scientific novelty lies in the development of a three-level model of circular value-added chains, encompassing organizational-economic, sectoral-cluster, and national levels, which ensures the coherence of circular processes and their integration into global markets. The practical significance of the research is that the implementation of circular approaches will promote the creation of closed resource-use cycles, generate new jobs, expand export potential, and strengthen the economic resilience of the state. The findings confirm that the transition from a linear to a circular development model is not only an environmental necessity but also a strategic imperative of the current stage of global development, forming the prerequisites for long-term economic growth, technological renewal, and enhanced international competitiveness of Ukraine.
Keywords: circular economy; value chains; global triggers; strategic imperatives; resilience; digitalization; innovative business models; national economic sustainability